Primer reporte de Peltophorus polymitus Boheman (Coleoptera: Curculionidae) en tres especies de Agave (Asparagaceae) en México/ First report of Peltophorus polymitus Boheman (Coleoptera: Curculionidae) on three species of Agave (Asparagaceae) in Mexico. - González-Hernández, Héctor; Figueroa-Castro, Pedro; Rubio Cortés, Ramón; W. Jones, Robert; Valdéz-Carrasco, Jorge M. (Instituto de Ecología, A.C., 2015)
Peltophorus polymitus Boheman (Coleoptera: Curculionidae) is recorded for the first time attacking Agave tequilana Weber var. Azul in Jalisco and Agave cupreata Trel. & Berger and Agave angustifolia Haw., in Guerrero. The variety of damages to Agave plants caused by this weevil are described.